SAT0414 Predictors of Functional Deterioration in Chinese Patients with Psoriatic Arthritis: A Longitudinal Study. (10th June 2014) - Leung, Y.Y.; Ho, K.-W.; Li, E. K.-M.; Li, M.; Kwok, L.-W.; Wong, P.C.; Li, T.K.; Zhu, T.Y.; Kun, E.E.; Tam, L.-S.
Abstract : Background: There is spare data from Asia on the longitudinal course of physical function in psoriatic arthritis (PsA). Objectives: We aim to describe variables associated with a deterioration of physical function in PsA in Chinese over a 6-year period. Methods: 125 consecutive patients with PsA fulfilled the CASPAR criteria from a rheumatology outpatient center were recruited to give sociodemographic and clinical data in 2006 to 2008. Follow up interviews were conducted in 2012 to 2013 to assess physical function using Health Assessment Questionnaire (HAQ). Regression models were constructed to determine baseline variables that predict physical function on follow up. Results: A total of 97 patients completed the follow up survey, with mean follow up time of 6.2 (±0.7) years, response rate 77.6%. PsA patients had poor physical function and health related quality of life (HRQoL) compared to normal population. There were 33% who improved in disability status and 41.2% had persistent minimal disability by HAQ categories (HAQ 0-0.49) over time. There were 14.4% of the patients who had persistent moderate disability (HAQ 0.5-1.50) and 10.3% had deterioration in disability status. There were 17.5% of patients who had deterioration in physical function as defined by an increment of HAQ score of more than 0.2 at follow up survey. Age, physical function at baseline and the number of damaged joint were significantly related HAQ at follow up. Conclusions: Chinese patients with PsA had had poor physical function and quality of life. One fifth of patient experienced deterioration of physical function over time. Joint damage and baseline physical function were important factors associated with poor physical function in PsA over time. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1100